2012
DOI: 10.1074/jbc.m112.377515
|View full text |Cite
|
Sign up to set email alerts
|

miR-218 Directs a Wnt Signaling Circuit to Promote Differentiation of Osteoblasts and Osteomimicry of Metastatic Cancer Cells

Abstract: Background: MicroRNAs control cell signaling during osteoblast differentiation. Results: miR-218, which is highly expressed in osteoblasts and cancer cells metastatic to bone, targets three inhibitors of Wnt signaling, Sclerostin, Dickkopf2, and secreted frizzled-related protein2. Conclusion: miR-218 promotes differentiation of normal osteoblast and the osteomimetic bone-homing properties of tumor cells. Significance: miR-218 may be a universal stimulator of Wnt-signaling during bone development and cancer pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
215
4
7

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 263 publications
(234 citation statements)
references
References 53 publications
8
215
4
7
Order By: Relevance
“…It has been shown that miR-218 expression is downregulated in many tumors including ESCC (15)(16)(17)(18)(19)(20) and is involved in cancer initiation and development (15)(16)(17)(18)(19)(20)(21)(22) SOT (38), Rob1 receptor (39) as well as LAmb3 (40), which are involved in several different signaling pathways, suggesting that miR-218 is a tumor suppressor miRNA and plays a crucial role in the initiation, development and metastasis of tumors. Therefore, we reasonably speculated that miR-218 suppresses the tumor growth of ESCC in vitro and in vivo by regulating multiple target genes.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that miR-218 expression is downregulated in many tumors including ESCC (15)(16)(17)(18)(19)(20) and is involved in cancer initiation and development (15)(16)(17)(18)(19)(20)(21)(22) SOT (38), Rob1 receptor (39) as well as LAmb3 (40), which are involved in several different signaling pathways, suggesting that miR-218 is a tumor suppressor miRNA and plays a crucial role in the initiation, development and metastasis of tumors. Therefore, we reasonably speculated that miR-218 suppresses the tumor growth of ESCC in vitro and in vivo by regulating multiple target genes.…”
Section: Discussionmentioning
confidence: 99%
“…These effects correlate with a decreased expression of Sfrp2, Sost, and Dkk2. Moreover, BMP and Wnt stimuli induce higher miR-218 levels, leading to the upregulation of b-catenin and Tcf1 (Hnf1a) expression and therefore linking miR-218 to a positive loop mechanism involving Wnt signaling (Hassan et al 2012). Dkk1 is also a miRNA target, leading to enhanced Wnt signaling.…”
Section: The Interplay Between Mirnas and Wnt/b-catenin Signalingmentioning
confidence: 99%
“…MiR-218 stimulates the Wnt pathway in breast cancer cells by directly targeting the Wnt inhibitors SOST, DKK2 and SFRP2 that have the potential to enhance the expression of osteoblastic genes in metastatic cells. 62 This osteomimetic gene expression has the potential to influence metastatic cell homing to the bone. An additional study found that miR-204, miR-211 and miR-379 regulate interleukin (IL)-11 expression in breast cancer cells.…”
Section: Tumor-intrinsic Mirna Regulation Of Bone Metastasismentioning
confidence: 99%